Assessment of the presence of mathematics processes Standards in an arithmetic problem solving activity (Edma 0-6: Educación Matemática en la Infancia, 2021)
Since Process Standards were introduced by the NCTM (2000) in the Principles and Standards for School Mathematics to promote greater mathematical competence in students, their relevance has grown. A competency-based approach in Early Childhood Mathematics incorporating the Process Standards requires indicators to assess and analyze their treatment. We analyze the presence of the Process Standards in a teaching activity with 5 years-old children on solving an arithmetic problem. We use the assessment tool proposed by Alsina and Coronata (2014).
Keywords: Arithmetic problems; Assessment; Early Childhood Mathematics; Multiplication; Mathematical processes Standards